Preliminary survey of Aphanomyces sp. associated with native and invasive crayfish in the Lower Susquehanna watershed of South Central Pennsylvania. Issue 1 (1st January 2020) - Butler, Elizabeth; Crigler, Patricia; Robbins, Glenn; Blair, Jaime E.
Abstract: The oomycete species, Aphanomyces astaci, is well known as the devastating causal agent of European crayfish plague. Despite assumptions of a North American origin, the prevalence and distribution of A. astaci in its presumed native range is unknown. In this study, we modified published PCR-based diagnostic methods to detect Aphanomyces sp. in both whole crayfish and in environmental DNA from bulk water samples. Putatively positive samples were sequence-verified as A. astaci, and pure cultures were obtained from four individual crayfish. Our results suggest that a single genotype of A. astaci is present in at least six out of ten locations sampled within the Lower Susquehanna watershed, and is associated with three non-native species, including Faxonius rusticus, the rusty crayfish. Aphanomyces were not detected directly from native crayfish, Cambarus bartonii, but both A. astaci and an unknown Aphanomyces species were detected from corresponding environmental DNA samples. Although North American crayfish are considered less susceptible to A. astaci infection, future studies should interrogate the impact of invasive species, such as the rusty crayfish, and land use changes on potential host-pathogen dynamics.